Effect of Service Quality Dimensions on Customer Satisfaction: A Comparative Analysis of Pakistan Telecom Sector - Muhammad ARSLAN; Maria IFTIKHAR; Rashid ZAMAN (Revista de Management Comparat International)
The purpose of this study is to establish the relationship between service quality and customer satisfaction. Two main dimensions of service quality were taken i.e. reliability and empathy. This is a quantitative analysis and the data was collected in the form of communication-based questionnaires. The sample size was 400 respondents and four main telecom service providers were considered for the study. The results were calculated by analytical software SPSS-20. It was concluded that service reliability and service empathy both have an effect on customer satisfaction. It was also determined that some factors were more satisfactory than the others. The findings of study reveal that percentages of customer satisfaction change with the service quality dimensions of reliability and empathy. Overall, it can be established that there is a significant relationship between customer satisfaction and service quality dimensions of empathy and reliability.